2021
DOI: 10.14311/ap.2021.61.0644
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary prospects of a Carnot-battery based on a supercritical CO2 Brayton cycle

Abstract: As a part of the change towards a higher usage of renewable energy sources, which naturally deliver the energy intermittently, the need for energy storage systems is increasing. For the compensation of the disturbance in power production due to inter-day to seasonal weather changes, a long-term energy storage is required. In the spectrum of storage systems, one out of a few geographically independent possibilities is the use of heat to store electricity, so-called Carnot-batteries. This paper presents a Pumped… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Analysing Figure 2b, which represents the heat engine used in the present work, the CO 2 leaving the turbine (HET) takes the thermal energy from the molten salts in the molten salts/CO 2 heat exchanger (MSHE) (8)(9) and transfers it to the cold stream in the high-temperature recuperator (HTR), reaching the condition of the turbine inlet. Once the hot stream has left the HTR, it transfers thermal energy again (10)(11) in the low-temperature recuperator (LTR) to the cold stream (13)(14). It can be observed that the cold mass flow rate in the LTR (high-pressure stream) is lower than the mass flow rate of the hot stream (low-pressure steam).…”
Section: Heat Enginementioning
confidence: 99%
See 2 more Smart Citations
“…Analysing Figure 2b, which represents the heat engine used in the present work, the CO 2 leaving the turbine (HET) takes the thermal energy from the molten salts in the molten salts/CO 2 heat exchanger (MSHE) (8)(9) and transfers it to the cold stream in the high-temperature recuperator (HTR), reaching the condition of the turbine inlet. Once the hot stream has left the HTR, it transfers thermal energy again (10)(11) in the low-temperature recuperator (LTR) to the cold stream (13)(14). It can be observed that the cold mass flow rate in the LTR (high-pressure stream) is lower than the mass flow rate of the hot stream (low-pressure steam).…”
Section: Heat Enginementioning
confidence: 99%
“…The cost of the heat exchanger was determined based on the cost of a baseline heat exchanger, which was adjusted by taking into account various factors, such as different materials, pressures, and other design features. The cost, C E (USD), was estimated using Equation ( 13), supported by Equation (14). Here, C b represents the cost of the baseline heat exchanger made of a base material (carbon steel) ($/ft 2 ) designed for a specific pressure range (cost based on 1982 data).…”
Section: Economic Modelmentioning
confidence: 99%
See 1 more Smart Citation